Screening and Assessment of Antimicrobial Susceptibility of Periodontopathic Bacteria in Peruvian Patients with Periodontitis: A Pilot Study - Aguilar-Luis, Miguel Angel (2021)
Background. Severe periodontal disease is highly prevalent worldwide, affecting 20% of the population between the ages of 35 and 44 years. The etiological epidemiology in Peru is scarce, even though some studies describe a prevalence of 48.5% of periodontal disease in the general population. Periodontitis is one of the most prevalent oral diseases associated with site-specific changes in the oral microbiota and it has been associated with a socioeconomic state. This study aimed to determine the etiology and resistance profile of bacteria identified in a group of Peruvian patients with periodontal disease. Methods. Six subgingival plaque samples were collected from eight patients with severe periodontitis. Bacterial identification was carried out by an initial culture, PCR amplification, and subsequently DNA sequencing. We evaluated the antibiotic susceptibility by the disk diffusion method. Results. Variable diversity in oral microbiota was identified in each one of the eight patients. The bacterial genus most frequently found was Streptococcus spp. (15/48, 31.3%) followed by Rothia spp. (11/48, 22.9%), Actinomyces spp. (9/48, 18.8%), and Eikenella spp. (4/48, 8.3%). The most common species found was Rothia dentocariosa (8/48, 16.7%). The antimicrobial susceptibility assay varied according to the species tested; however, among all the isolates evaluated, Actinomyces naeslundii was resistant to penicillin and tetracycline; Eikenella corrodens was resistant to dicloxacillin; and Rothia dentocariosa was resistant to amoxicillin + clavulanic acid and metronidazole but also susceptible to trimethoprim-sulfamethoxazole. Conclusions. The most prevalent periodontal bacterium found in this study was Rothia dentocariosa. Specific antimicrobial therapy is required to improve the treatment outcomes of patients with periodontal disease and avoid antibiotic resistance.